Using Speaking Worksheets in Enhancing Accuracy in EFL Adultsâ Spoken English - Chandra, Julian; Hayati, Amal (UICELL, 2017)
With the development of teaching spoken English more oriented to fluency, obviously accuracy in spoken English is much neglected. Additionally, the changing language pedagogy into more integrated way results in how integrating linguistic components in the teaching spoken English becomes a challenging task for teachers. Optionally, integrating form and meaning-based activities into teaching spoken English is suggested to be able to raise EFL learnersâ awareness to address not only language fluency but also accuracy. This study was aimed to find the effect of using guided speaking worksheets towards senior high school studentsâ accuracy in spoken English. Pre-test and post-test design was employed in this quasi-experimental research. With total random sampling technique, 22 senior high school students  were taken as the research sample of whom 11 were randomly assigned into experimental group, while the other were randomly assigned into control group. Samples in experimental group were received self-made speaking worksheets with target vocabulary, expressions and grammar attached for students to practice spoken English. Oral test was the research instrument in which its validity and reliability were determined by its content validity and inte-rrater coefficients correlation. With nonparametric analysis by MannWhitney U formula to test hypothesis. It was found that U-observed (-15) was smaller than Utable (34). It means that H0 was rejected and H1 was accepted. The conclusion is that there was significant effect of using self-made speaking worksheet towards the studentsâ accuracy in teaching spoken English. The research findings lead to a discussion of its recommendation to be used in teaching spoken English.